2006
DOI: 10.1116/1.2393252
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of molecular ruler technology for nanoscale patterning

Abstract: Articles you may be interested inDeep UV patterning of 3-amino-propyl-triethoxy-silane self-assembled molecular layers on alumina By combining optical lithography and chemical self-assembly, the authors circumvent the limitations of photolithography and provide a parallel, low-cost alternative to fabricate sub-50 nm features. Self-assembled multilayers, composed of alternating layers of ␣ , -mercaptoalkanoic acids and copper ͑II͒ ions ͑"molecular rulers"͒, are used as an organic sidewall spacer resist on initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…13 In 1991, Evans et al 14 showed the forming of multilayer films using ionic interaction between ␣ , -mercaptoalkanoic acids ͑HS͑CH 2 ͒ x COOH͒ and copper ions͑Cu 2+ ͒. [16][17][18] Es-pecially, Anderson and co-workers [19][20][21][22] at Pennsylvania State University reported several attempts to fabricate various nanogaps. The acid surface is then converted to a copper salt and a second layer can be adsorbed onto the copper surface; it has been seen that thiols will readily adsorb onto copper.…”
Section: Introductionmentioning
confidence: 99%
“…13 In 1991, Evans et al 14 showed the forming of multilayer films using ionic interaction between ␣ , -mercaptoalkanoic acids ͑HS͑CH 2 ͒ x COOH͒ and copper ions͑Cu 2+ ͒. [16][17][18] Es-pecially, Anderson and co-workers [19][20][21][22] at Pennsylvania State University reported several attempts to fabricate various nanogaps. The acid surface is then converted to a copper salt and a second layer can be adsorbed onto the copper surface; it has been seen that thiols will readily adsorb onto copper.…”
Section: Introductionmentioning
confidence: 99%
“…Following our previous work, 15 the LER for imprint molds is improved for the following reasons. The Au thin films are removed after molecular-ruler processing, and the Cr adhesion layer is retained on the quartz substrates.…”
mentioning
confidence: 99%
“…1, Photolithography, EBL, or other methods are used to create the first generation ͑parent͒ Cr/ Au features. [12][13][14][15]22,23 A self-assembled multilayer film comprising alternating layers of ␣, -mercaptoalkanoic acids and Cu 2+ ions ͑molecular rulers͒ binds selectively to the parent structures and not to the underlying quartz substrate. The overall thickness of this organic thin film is selected by both the numbers and thicknesses of the molecular layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular monolayers can be patterned via conventional lithographic techniques (e.g., photolithography) , but are more commonly patterned using low-cost and high-throughput soft-lithographic methods. ,,, Conventional soft lithography (e.g., microcontact printing, μCP), involves the additive patterning of SAM molecules onto surfaces by transfer of molecular inks via contact of patterned polydimethylsiloxane (PDMS) stamps with the corresponding surfaces. While μCP has significantly advanced the field of SAM patterning, it is inherently limited in the resolution of features produced due to lateral diffusion of ink molecules during and after the patterning is performed. , Advances in soft lithography have improved feature resolution ,, (e.g., polymer pen lithography and microdisplacement printing) …”
mentioning
confidence: 99%